Bridging the gap: ICU nurses’ knowledge and perceived practices in meeting family needs - Halain, Azura Abdul; Lam, Soh Kim; Japar, Salimah; Geok, Soh Kim (Universiti Putra Malaysia Press, 2025)
Introduction: The admission of a relative to the Intensive Care Unit (ICU) is highly stressful for family members. Hence, accurately assessing and responding to the family needs of critically ill patients may increase family satisfaction with care, as well as promote trust and confidence to the nurses. Aim: To assessed nurses’ knowledge of family needs and examined their present practices in meeting those needs. Methods: A cross-sectional study was conducted using convenience sampling to select 187 participants from an ICU in a government hospital in Malaysia. The Critical Care Family Needs Inventory (CCFNI) was used to assess nurses’ knowledge and practices. Data were analyzed using SPSS version 25.0. Results: Out of 187 participants, 64.7% (121) had good knowledge, and 60.96% (114) demonstrated good practices in addressing family needs. Family needs were prioritized as follows: information (44.9%), support (29.4%), proximity (10.2%), comfort (9.6%), and assurance (5.9%). Significant correlations were found between socio-demographic factors and knowledge scores, specifically years of ICU experience and completion of ICU post-basic. Practice scores were also significantly correlated with years of ICU experience (p-value <0.05). However, Spearman’s correlation test showed no significant relationship between high knowledge scores and practice scores (r = -0.098, p = 0.183). Conclusion: This result suggests that while nurses may possess good knowledge regarding family needs, this knowledge does not always translate into consistent and effective practices, highlighting the importance of continuous training and support to bridge this gap and ensure optimal care for family members of patients in ICU.